The Mediating Role of Managerial Efficiency in the Relationship between Corporate Financial Characteristics and Market Value: An Empirical Study of a Sample of Iraqi Banks (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aimed to explore the mediating role of managerial efficiency on the relationship between the company's financial characteristics and its market value in a sample of 10 Iraqi banks listed on the Iraq Stock Exchange for the period from 2013 to 2023. It relied on the descriptive analytical approach and the manual content analysis method to measure the variables. The research concluded that there is a significant positive effect of bank size, profitability, and financial leverage on market value. The research also concluded that the mediation of managerial efficiency does not affect the relationship between the company's financial characteristics and its market value.
Keywords: Managerial Efficiency; Financial Characteristics; Market Value